Development of Hardware and Software for a Non-Invasive Glucometer Based on A Microcontroller - Docent. Khaydarov A.Kh; Docent Eltazarov B.T; Sen. Lec.Kimizbayeva A.E; Master Tuychiev F.F. (Genius Publishing Group, 2023)
Diabetes occurs when blood glucose levels exceed a threshold. Existing blood glucose testing methods are invasive methods based on needles that are inserted into a person's body to take a blood sample from the body, and then it is transferred to disposable test strips for chemical processing to determine the amount of glucose present in it. However, for patient pain relief and the use of test strips, these techniques have led to the development of non-invasive methods. Non-invasive methods use a near-infrared sensor to measure glucose levels at the fingertip without the use of needles or test strips. A near infrared (NIR) optical signal is transmitted through one side of the fingertip and then received on the other side of the fingertip, which predicts the molecular blood glucose count by analyzing the change in intensity of the received signal after it has passed. In this work, we have developed such a system using a microcontroller and other electronic parts. Before that, we developed a simulation model in the Proteus environment
Keywords: diabetes mellitus; NIR method; invasive and non-invasive glucometer